(untitled) (Bangladesh Journal of Medical Biochemistry, 2018)
Hypercholesterolemia is one of the important causes of cardiovascular disease related mortality and morbidity and recently it has become a significant issue in public health problem of developing countries. The purpose of the study was to see the effect of glycine max (soy bean) on serum lipid profile of experimentally induced hyperlipidemic rats. Hypercholesterolemia was induced by high cholesterol diet containing 1% cholesterol in olive oil. This study was done on 24 long Norwegian rats (Rattus norvegicus) weighing about 200-210 gram. For convenience, the study was divided into Experiment I and Experiment II. In experiment I, 12 rats were divided into two groups- Group A (n = 6, control group) fed on laboratory diet and Group B (n=6) fed on laboratory diet and soy bean extract for 35 days. In experiment II, the remaining 12 rats were divided into 2 groups, Group C (n=6) were fed on laboratory diet and high cholesterol diet (HCD) for 35 days and Group D (n=6) were fed laboratory diet and high cholesterol diet on initial 10 days and soy bean extract was added along with high cholesterol diet for next 25 days. Serum TC, TG, LDL-C and HDL-C were measured after 35 days. HCD increased TG, TC and LDL-C significantly in group C. Glycine max (soy bean) treated group showed that it decreased plasma TC, TG and LDL-C in experimentally induced hyperlipidemic rats but Glycine max (soy bean) did not show any significant lipid lowering effect in normolipidemic rats. The results of this experimental study indicate that Glycine max can act as a cholesterol lowering agent and thereby can improve cardiovascular functions. Bangladesh J Med Biochem 2017; 10(1): 21-26